2022
DOI: 10.1039/d1nj04719a
|View full text |Cite
|
Sign up to set email alerts
|

Carbopol 940 hydrogel containing curcumin-loaded micelles for skin delivery and application in inflammation treatment and wound healing

Abstract: Inflammation and excessive reactive oxygen species production are main reason for slow wound healing, which needs an efficient therapy in clinic. In the paper, curcumin-enveloped methoxy poly(ethylene glycol)-poly(-valerolactone)-poly(-caprolactone) (MPEG-PVL-PCL) micelles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…39 Numerous studies have demonstrated that the flavonoids and Carbopol 940 hydrogel possess wound-healing properties due to their well-acclaimed anti-inflammatory, antioxidant, re-epithelialization, and angiogenesis effects. 14,40–43 In our previous report, QU in combination with LU enhanced the antibacterial and antibiofilm efficacy synergistically, decreasing the membrane permeability and down-regulating the expression of multiple biofilm-related genes. 30 Besides, QU and LU are known for their powerful anti-inflammatory and antioxidant potency due to the resonance stability of the phenoxyl radical, 31,32 which support their potential use in wound healing.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…39 Numerous studies have demonstrated that the flavonoids and Carbopol 940 hydrogel possess wound-healing properties due to their well-acclaimed anti-inflammatory, antioxidant, re-epithelialization, and angiogenesis effects. 14,40–43 In our previous report, QU in combination with LU enhanced the antibacterial and antibiofilm efficacy synergistically, decreasing the membrane permeability and down-regulating the expression of multiple biofilm-related genes. 30 Besides, QU and LU are known for their powerful anti-inflammatory and antioxidant potency due to the resonance stability of the phenoxyl radical, 31,32 which support their potential use in wound healing.…”
Section: Discussionmentioning
confidence: 89%
“…13 Recently, the curcumin-loaded methoxy poly(ethylene glycol)-poly(delta-valerolactone)poly(epsilon-caprolactone) micelle-embedded Carbopol 940 hydrogel was demonstrated to be a potential candidate for the treatment of skin inflammation and full thickness wound healing. 14 Moreover, a few herbal plant extracts or purified active compounds formulated into Carbopol 940 hydrogel preparations have been used for wound healing. [15][16][17] Natural products have always been significant resources of alternatives of antibiotics against S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…As the KTTKS has a cysteamine group at the C-terminus, it can be covalently patched on the MEL linker co-assembled with PNVs through a thiol-maleimide reaction. Curcumin was selected as a model active ingredient that can accelerate fibroblast proliferation 33,34 and was encapsulated in the core, thus producing CPNV KTTKS (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…29–31 Therefore, it is imperative to develop PDA-based injectable hydrogels through facile preparation. 32…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Therefore, it is imperative to develop PDA-based injectable hydrogels through facile preparation. 32 The metal-ligand coordination interaction with a capacity to produce hydrogels with high mechanical properties has attracted increasing attention to preparing advanced hydrogels for wound healing management. 33 Many metal ions have shown crucial roles in tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%